- Strategi Untuk Meningkatkan Capaian Standar Pelayanan Minimal (SPM) Pada Urusan Pendidikan, Kesehatan Dan Pekerjaan Umum Dan Penataan Ruang: (Studi Kasus pada Pemerintah Kota Magelang) - Sarastri, Linggar; Indarto, Indarto; Wardoyo, Paulus (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
The purpose of this study was to find out and analyze the strategies that can be used by the City Government of Magelang in implementing SPM (Minimum Service Standards). The implementation of SPM is an effort to fulfill basic services in Mandatory Government Affairs for the citizens of the city of Magelang, covering education, health, public works and spatial planning, public housing and residential areas, peace, public order, and community protection, and social affairs. The achievement of the 100% service target is a measure of the success of SPM implementation. The analytical method in this research is a qualitative case study. The data used is primary data obtained through interviews, observation and documentation which includes the efforts, constraints and strategies of the City Government of Magelang in achieving 100% of the SPM implementation target. The research findings show that there are several efforts as a strategy that can be carried out by the City Government of Magelang in targeting the implementation of SPM. These efforts include establishing the Mayor's Policy on SPM Fulfillment, establishing the Mayor's and Head of Service's Performance Agreement, conducting SPM Target Formulation Consultations with the Technical Ministries, conducting database validation, setting plans for SPM fulfillment in the RPJMD, formulating Action Plans, Cross-Sectoral Coordination, outreach and educating related parties, strengthening supervision, making routine real time evaluation applications, enforcing sanctions and establishing channels for complaints. This is intended so that the SPM implementation target is achieved 100% so that the fulfillment of basic services for Magelang city residents can be carried out as optimally as possible. Key iwords i: istrategy, iSPM